Retsmedicinske findestedsundersøgelser - Peter Mygind Leth; Stine Hovvang; Asser Hedegård Thomsen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract During the years 2000 to 2020 the Department of Forensic Medicine at the University of Southern Denmark performed 293 medical crime scene investigations in Southern Denmark involving 320 deceased (200 men). The medical examiner was called out in homicides (24%), suspicious cases (58%), fire related deaths (15%) and bone findings (2%). The medical examiner was responsible for the medical examination of corpses in cooperation with the crime scene  technicians. The goal was to determine the cause of death, the manner and mechanism of death, and the time of death. Most were autopsied after the crime scene investigation. The scene was considered suspicious if displaced or broken furniture, or bloodstains, were found. Actions by alcohol or drug intoxicated individuals may resemble a crime scene. Blood stains can arise from natural causes. Suicide by stabbing or shooting may give rise to a suspicious scene, as may deaths during autoerotic procedures and deaths due to hypothermia. Most crime scenes were indoors, but a quarter occurred outside. The deceased included a high proportion of individuals with chronic alcoholism (36%) and many suffered from psychiatric disease (23%). Based on autopsy, manner of death was determined to have been homicide (30%), accident (27%), suicide (18%), natural death (14%) and unknown causes (6%). 5% was not autopsied. The pattern of lesions are important in determining the mechanism of death, but must always be viewed in relation to findings at the scene and the deceased’s history. Medical crime scene investigation underwent improvements during the period, most notably the introduction of DNA-trace analysis. Photo and video documentation also improved. Photogrammetry and the use of drones are being introduced.